Sosialisasi Perbaikan Manajemen Reproduksi pada Ternak Sapi Potong di Desa Laitutun Kecamatan Letti Kabupaten Maluku Barat Daya - Arnold Ismael Kewilaa; Albertus Sairudy; Barnabas Gairtua; Jen Merlinda Lekipiou; Yokbet Yerusa; Adelcy Putriny Romkeny; Ludia Haprekkunarey; Lili Marlen Nyainleta; Viktor B. Untajana; Yulius A. Aktawelora; Novita Maupula; Agnes Serpiela; Erna Yanti Laumaly; Weli Apriliani Salmanu; Olinda Maria Maahury; Dewi Rosita Rupisay (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
The purpose of this activity is to conduct outreach on improving reproductive management in beef cattle. This activity was carried out in Laitutun Village, Letti District, Southwest Maluku Regency, which took place in September 2025. The target of this activity was beef cattle breeders in Laitutun Village. The implementation of this activity includes two stages, namely: the preparation stage and the implementation stage. In the preparation stage, surveys, licensing coordination, and problem identification were conducted, to identify problems in the livestock sector. In the implementation stage, outreach was conducted on improving reproductive management in beef cattle in Laitutun Village. The material presented was reproductive management and various reproductive problems that can hinder the increase in the beef cattle population in Laitutun Village. This outreach activity involved all Laitutun Village Staff and the livestock community who raise beef cattle. The conclusion of this activity was increased information, knowledge, and understanding of good reproductive management, increased knowledge about the cycle and signs of estrus as well as the right time for mating and producing pregnancy, and increased motivation of the livestock community in developing the beef cattle business by increasing its population.